Beyond the Categorical Distinction Between Borderline Personality Disorder and Bipolar II Disorder Through the Identification of Personality Traits Profiles - Villarroel, Juana; Salinas, Valeria; Silva, Hernán; Herrera, Luisa; Montes, Cristián; Jerez, Sonia; Vöhringer, Paul A.; Bustamante, Maria Leonor (Frontiers in Psychiatry, 2020)
BACKGROUND: The relationship between borderline personality disorder (BPD) and bipolar II disorder (BDII) is not clearly understood. We propose using personality traits to describe them, beyond the categorical distinction. METHODS: Five-Factor Model personality traits were measured in 73 individuals with either BPD or BDII. Latent class cluster analysis was applied to the sample. RESULTS: A three-cluster model resulted the best fit to the data, where all clusters had high Neuroticism and Extraversion scores but differed widely on the other traits. The clusters boundaries did not match the categorical diagnosis. CONCLUSIONS: Our sample showed significant heterogeneity on personality traits, which can have a relevant effect on the outcome of each disorder and was not captured by the categorical diagnosis. Thus, we advocate for a multivariate approach as a better way to understand the relationship between BPD and BDII.